A review on Illicit drugs and biosensing advances for its rapid detection. (February 2022) - Anzar, Nigar; Suleman, Shariq; Parvez, Suhel; Narang, Jagriti
Graphical abstract: Highlights: Current status of fast, rapid and on spot diagnosis of rape drugs. Techniques including identification of several majorly known drugs are illuminated. Biosensing methods with their future development and possibilities are summarised in this review. Abstract: Drugs are extracted from plants and synthetic chemicals for their medicinal values and healing properties, these various drugs present worldwide can be of uncountable importance with each of it having different medicinal values that may help in the treatment of numerous lethal diseases, but on the other hand Illegitimate drug-associated incidents like sexual assaults and traffic accidents are gaining recurrence proportions worldwide. As for the clinical and forensic use to spot the evidences in case of sexual assaults the detection of drugs in biological fluids can be very important. Furthermore, there is widespread drug usage at some crucial workplaces, which can cause serious safety issues. This article would shed some light on the drugs that are widely involved in sexual assaults, as well as the many conventional techniques for detecting illicit drugs that have been developed. Ultraviolet spectroscopy, mass spectrometry (MS), thin layer chromatography, Microcrystalline test, infrared spectrometry, ion mobility spectrometry (IMS), Raman spectroscopy, Xray diffraction, spot/colour test, and immunoassay are some of the more prevalent procedures. These methods are primarily employed to identify illicit drugs, but they are both costly and time-consuming. For the fast diagnosis of these drugs, various sensors such as colorimetric sensors, fluorescence sensors, and electrochemical sensors were developed for most popular rape medications, including cocaine, cannabis, methamphetamine, fentanyl, morphine, heroin, and benzodiazepine (diazepam, oxazepam, clonazepam etc).